Learning from Firefighters: A Goal-Free Evaluation of Fire Disaster Mitigation Program for Early Years Students - Damayanti, Nina Afria; Hia , Semadi Warni; Waruwu , Wiwin Kristiani; Kartika , Jelni (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2024)
Field trips are not merely an escape from the classroom; they are powerful tools to bridge theoretical concepts with real-world experiences. The fire disaster mitigation program for early learners at a local fire station introduced children to essential fire safety practices while reshaping their understanding of heroism and inspiring new aspirations. This study aimed to evaluate the program's implementation, its impact on children’s understanding of fire safety, and the development of critical thinking and career aspirations. Using a qualitative approach, data were collected through direct observation, interviews with students, teachers, and parents, and an analysis of program materials. Thematic analysis revealed that children gained a deeper appreciation for real-world heroism, comparing firefighters to figures like Captain America and Iron Man, while also reflecting critically on fire safety concepts, such as the importance of safe assembly points in their daily environments. Additionally, the program sparked new career aspirations among the children, particularly among boys, although gender stereotypes persisted with fewer girls expressing interest in firefighting. Despite its strengths, such as engaging presentations and hands-on simulations, the program exhibited limitations, including minimal parental involvement and a lack of diverse role models. These findings suggest that targeted improvements, such as incorporating follow-up activities, enhancing parental engagement, and introducing gender-inclusive narratives, could significantly enhance the program’s impact.